Micro-credentials in Malaysian higher education: a comprehensive case study approach - Cheng, Jack Kie; Yong, Irene Seok-Ching; Ch’ng, Chee Keong; Lim, Huai Tein (Springer, 2024)
Micro-credentials have become increasingly popular in the modern job market due to the ability to address rapid changes in various industries. These credentials offer flexibility, targeted and tailored learning experiences that fill specific skill gaps while preparing learners for job roles. In the hope of capitalizing on the advantages of this flexible education, higher education institutions in Malaysia are increasingly adopting micro-credentials. Although all micro-credentials offered in Malaysia’s higher education institutes must conform to the Malaysian Qualifications Agency’s standards and regulations, the set-ups and implementation, however, are flexible depending on the institution’s ecosystem. As micro-credentials are relatively new in Malaysia and the references to success stories are usually from overseas universities, which have different settings and environment. Therefore, there is a need for a comprehensive overview of micro-credentials implementation in the context of Malaysian higher education institutions. This study adopted a qualitative case studies approach on three universities in Malaysia, which represent the public and private universities with different micro-credentials implementation competence. Collation of insights, which includes comparisons on the composition of the working committee, sustainability strategies, and collaboration efforts are documented. An elaborate suggestion for micro-credentials newcomers is also included in this study through a proposed core team composition and detailed implementation pathway. Ultimately, this study contributes to providing potential micro-credentials providers in Malaysia with a reference to micro-credentials best practices.